Effect of various nanofillers on the insulating properties of polyethylene composites - Natcha Muenphan; Wanwilai Vittayakorn (Ferroelectrics, 2022)
This work focuses on the preparation of various inorganic nanoparticles i.e. Al2O3, SiO2, TiO2 including the waste glass powder filled in high-density polyethylene (HDPE H455JA) matrix to create high-performance composites. The glass powder prepared from broken windowpane was used in this study in order to use as a guideline to find substitutes for commercial materials and also add value to waste and reduce costs. The 2 wt% of each filler was weighed and mixed with HDPE to create a composite by using a simple mold casting technique. The physical, chemical and electrical properties were investigated for all samples. The results show that the εr value of the pure HDPE and the HDPE-based composites are approximately the same in all frequencies and the εr of pure HDPE tends to decrease about 7.8% at elevated temperature, whereas the εr value of composites is less decreased at higher operating temperatures for all samples which can imply that the composites are more capable of operating at higher temperatures than pure HDPE itself. For the electrical resistivity, the ρ value gradually increases at elevated temperature for all samples and the composites show a higher ρ value than that of pure HDPE.
Keywords: Dielectric materials and actuators; High voltage insulation and dielectric phenomena; Polymer Nanocomposites and Properties